2018
DOI: 10.1097/qad.0000000000001810
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and inflammatory biomarkers in perinatally HIV-infected and HIV-exposed uninfected children

Abstract: PHEU and PHIV have modest, significant differences in serum levels of specific inflammatory and active myocardial injury biomarkers. Higher biomarker levels were associated with lower LV mass and shifts in LV structure. Further study is warranted on the longitudinal role of cardiac and inflammatory biomarkers for targeting interventions among PHIV and PHEU youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Furthermore, Osuji and colleagues showed a 2.5 reduction in IL-6 levels just one year after ART initiation ( Osuji et al., 2018 ). In similar recent studies, comparable levels of IL6 were observed between viral suppressing HIV+ children (from Africa and US) and their uninfected counterparts, further confirming our hypothesis ( Wilkinson et al., 2018 ; Dirajlal-Fargo et al., 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Osuji and colleagues showed a 2.5 reduction in IL-6 levels just one year after ART initiation ( Osuji et al., 2018 ). In similar recent studies, comparable levels of IL6 were observed between viral suppressing HIV+ children (from Africa and US) and their uninfected counterparts, further confirming our hypothesis ( Wilkinson et al., 2018 ; Dirajlal-Fargo et al., 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Factors that can cause intracellular calcium uptake and efflux will result in calcium overload, thereby compromising the patient's ventricular diastolic function [ 11 – 13 ]. In addition, cardiomyocyte stiffness, left ventricular pressure overload, volume reduction, and heart rate changes are also associated with DHF [ 14 , 15 ]. Echocardiography is a widely used diagnostic method in clinical practice that can objectively and accurately evaluate the cardiac function of patients and monitor the changes in cardiac function in real time, with the advantages of noninvasiveness, easy operation, and repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…Long term HIV related immune activation may further contribute to this CNS pathology. HIV related systemic immune activation as indicated by systemic inflammation, monocyte and endothelial activation, with raised CRP, MCP-1, soluble CD14 (sCD14), soluble intercellular adhesion molecule-1 (sICAM-1) and vascular cell adhesion molecule-1 (sVCAM-1), IL-1, IL-6, IL-8, IL-10, IL-18, TNF-α), and soluble TNF receptor II (sTNF-RII) concentrations is reported in well treated PHIV ( 70 73 ). In HIV infected adults, elevated sCD14 levels in CSF were associated with increased levels of CSF neurofilament light-chain (NfL) levels and reduced brain tissue levels of the neurometabolite N-acetylaspartate (NAA) ( 74 , 75 ).…”
Section: (Neuro)inflammatory Markers In Pediatric Hivmentioning
confidence: 99%